Expand the expressions and simplify.

5(x + 4) + 3(x + 2) = answer box

4(x + 3) + 2(x − 4) = answer box

4(x + 2) + 2(x + 5) = answer box

A. 8x+ 4

B. 8x+ 26

C. 6x + 4

D. 7x - 18

1 answer

5(x + 4) + 3(x + 2)
= 5x + 20 + 3x + 6
= 8x + 26

4(x + 3) + 2(x − 4)
= 4x + 12 + 2x - 8
= 6x + 4

4(x + 2) + 2(x + 5)
= 4x + 8 + 2x + 10
= 6x + 18

Therefore, the answers are:

5(x + 4) + 3(x + 2) = 8x + 26 (B)

4(x + 3) + 2(x − 4) = 6x + 4 (C)

4(x + 2) + 2(x + 5) = 6x + 18
Similar Questions
  1. Answer the questions:Expand 5(y + 2). Expand -5(-3 - 11g). Expand 1/3(q - 6). Expand 2/5(-5c + 10). Expand -7/6(3g + 2).
    1. answers icon 4 answers
  2. Simplify Algebraic Expressions Quick Check1 of 51 of 5 Items Question Simplify 4x + 8x using the properties of operations.(1
    1. answers icon 1 answer
  3. Are the expressions 3−(4x+1) and 4−4x equivalent?A. Yes, they are because both expressions simplify to 4−4x. B. Yes, they
    1. answers icon 1 answer
  4. Simplify Algebraic Expressions Quick Check3 of 53 of 5 Items Question Simplify 2a − 4b +7 + 8a + 6b − 2.(1 point) Responses
    1. answers icon 1 answer
more similar questions